Financial statement analysis and security valuation - Penman, Stephen S. (Boston : McGrow-Hill, 2007)
Business
Keywords: Financial statement; Security valuation; Valuation analysis; Accountin analysis; Risk analysis; Cash accounting; Accural accounting